Biomimetic catalytic aerobic oxidation of C–sp(3)–H bonds under mild conditions using galactose oxidase model compound CuIIL. Issue 33 (5th August 2022) - Liu, Xiao-Hui; Yu, Hai-Yang; Huang, Jia-Ying; Su, Ji-Hu; Xue, Can; Zhou, Xian-Tai; He, Yao-Rong; He, Qian; Xu, De-Jing; Xiong, Chao; Ji, Hong-Bing
Abstract : A biomimetic catalytic approach for the aerobic oxidation of C–sp(3)–H bonds using galactose oxidase model compound was developed. EPR showed that the Cu I -radical intermediate species was critical for O2 activation. Abstract : Developing highly efficient catalytic protocols for C–sp(3)–H bond aerobic oxidation under mild conditions is a long-desired goal of chemists. Inspired by nature, a biomimetic approach for the aerobic oxidation of C–sp(3)–H by galactose oxidase model compound Cu II L and NHPI ( N -hydroxyphthalimide) was developed. The Cu II L–NHPI system exhibited excellent performance in the oxidation of C–sp(3)–H bonds to ketones, especially for light alkanes. The biomimetic catalytic protocol had a broad substrate scope. Mechanistic studies revealed that the Cu I -radical intermediate species generated from the intramolecular redox process of Cu II LH2 was critical for O2 activation. Kinetic experiments showed that the activation of NHPI was the rate-determining step. Furthermore, activation of NHPI in the Cu II L–NHPI system was demonstrated by time-resolved EPR results. The persistent PINO (phthalimide- N -oxyl) radical mechanism for the aerobic oxidation of C–sp(3)–H bond was demonstrated.